Application of tools geoprocessing to aid in monitoring of the water resources quality on Silveira Martins - Santos, Tiago Pereira dos; Moraes, Liliane Milani de (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
One of the main causes of pollution and changes in water resources is the growing urbanization, what happens due to improperly used by residences to dispose their effluents. In this context, this study analyzes the status of water resources in the municipality of Silveira Martins - RS. To characterize the watersheds of the county, were used geoprocessing tools and a diagnosis of sanitation. this purpose a sample of 162 questionnaires, that after the results assisted in the preparation of a georeferenced map of the answers. And, were made qualitative and quantitative analyzes of water samples collected at three monitoring points in the microbiology laboratory of the Federal University of Santa Maria. Information was gathered on waterborne diseases in the hospital county Silveira Martins. This information helped map and locate as using geoprocessing tools each address noted on the medical record of attendance, and, after mapping the records of diarrheal diseases, we obtained the percentage of cases that are located in the study area.